Proceedings of the 55th Annual Meeting of the Association For Computational Linguistics (Volume 1: Long Papers) 2017
DOI: 10.18653/v1/p17-1092
|View full text |Cite
|
Sign up to set email alerts
|

Neural Discourse Structure for Text Categorization

Abstract: We show that discourse structure, as defined by Rhetorical Structure Theory and provided by an existing discourse parser, benefits text categorization. Our approach uses a recursive neural network and a newly proposed attention mechanism to compute a representation of the text that focuses on salient content, from the perspective of both RST and the task. Experiments consider variants of the approach and illustrate its strengths and weaknesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
122
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(126 citation statements)
references
References 31 publications
(48 reference statements)
0
122
1
Order By: Relevance
“…Only a few works have attempted to parse discourse relations for out-of-domain problems such as text categorizations on social media texts; Ji and Bhatia used models which are pretrained with RST DT for building discourse structures from movie reviews, and Son adapted the PDTB discourse re-lation parsing approach for capturing counterfactual conditionals from tweets (Bhatia et al, 2015;Ji and Smith, 2017;. These works had substantial differences to what propose in this paper.…”
Section: Related Workmentioning
confidence: 97%
See 1 more Smart Citation
“…Only a few works have attempted to parse discourse relations for out-of-domain problems such as text categorizations on social media texts; Ji and Bhatia used models which are pretrained with RST DT for building discourse structures from movie reviews, and Son adapted the PDTB discourse re-lation parsing approach for capturing counterfactual conditionals from tweets (Bhatia et al, 2015;Ji and Smith, 2017;. These works had substantial differences to what propose in this paper.…”
Section: Related Workmentioning
confidence: 97%
“…Researchers who, instead, tried to build the end-to-end parsing pipelines considered a wider range of approaches including sequence models and RNNs (Biran and McKeown, 2015;Feng and Hirst, 2014;Ji and Eisenstein, 2014;Li et al, 2014). Particularly, when they tried to utilize the discourse structures for out-domain applications, they used RNNbased models and found that those models are advantageous for their downstream tasks (Bhatia et al, 2015;Ji and Smith, 2017).…”
Section: Related Workmentioning
confidence: 99%
“…Weighted sentences can be aggregated using average pooling or max pooling. Prior work (Jiang et al, 2016;Ji and Smith, 2017) have explored some of these combinations but not all of them. In the ablation experiments, we try all combinations and we find that the (sigmoid, max pooling) attention gives the best result.…”
Section: Bag Encoder Architecturementioning
confidence: 99%
“…Understanding a document's discourse-level organization is important for correctly interpreting it, and discourse analyses have been shown to be helpful for several NLP tasks (Bhatia et al, 2015;Ji and Smith, 2017;Feng and Hirst, 2014b;Ferracane et al, 2017). A popular formalism for discourse analysis is Rhetorical Structure Theory (RST) (Mann and Thompson, 1988) (Fig.…”
Section: Introductionmentioning
confidence: 99%